Anti-microbial properties of the phenolic substances from some species of the genus Garcinia L - Chau, Truong Van; Quang, Tran Hong; Lien, Do Ngoc (Academia Journal of Biology, 2015)
The phenolic substances from two species of the genus Garcinia L. extracted by ethanol or/and methanol were analyzed by silicagel thin layer chromatography and then studied on the anti-microbial capacity to the strains of the hospital infectious bacteria (Staphylococcus aureus and Pseudomonas aeruginosa). The resultats  showed that:The extract by ethanol or methanol from the Garcinia mangostana fruit cortex has at least 16 bands of the phenolic substances while that from the Garcinia oblongifolia fruit cortex has 8 bands The obvious anti-microbial capacity to the Staphylococcus aureus and Pseudomonas aeruginosa strains of the phenolic substances from Garcinia mangostana and Garcinia oblongifolia was demonstrated by agar-agar diffusion technique.